Clinicopathological profile of colorectal cancer managed at a university teaching hospital, Nepal - Paudyal, Sanjaya; KC, Shiva Raj; Maharjan, Shantabir; Shah, Surendra; Giri, Niraj; KC, Samyukta; Sigdel, Bidhan (Journal of Patan Academy of Health Sciences, 2019)
Introductions: Colorectal carcinoma is the third most common cancer worldwide. The incidence is increasing in developing countries including Nepal. The aim of this study is to find out the clinicopathological pattern of colorectal carcinoma locally. Methods: Data were recorded retrospectively by reviewing the charts of the patients who were diagnosed and treated for in patients having colorectal cancer managed during three years period of 2016-9 at Patan Hospital, the university teaching hospital of Patan Academy of health sciences, Nepal. Clinicopathological profile, age, gender, surgery, histopathological findings were descriptively analised. Results: There were 36 colorectal cancer patients, male 20 (56%) and females 16 (44%), mean age 56.9 years (range 24 to 89). Curative surgery was possible in 17 (47.2%) and adenocarcinoma of moderate differentiation was found in 25 (70%) of the resected specimen. Conclusions: Colorectal carcinoma was found in old age, slightly more in male than female, adenocarcinoma being most common histology type.